IMPLEMENTATION OF MONTESORI CURRICULUM MANAGEMENT IN IMPROVING THE QUALITY OF LEARNING IN ASKARA MONTESORI KINDERGARTEN - Yayat Suharyat; Iin Kusmawati; Pauzan Haryono; Ibnu Muthi (International Journal of Social Science, 2022)
This study aims to determine the implementation of Montesori curriculum management along with the supporting and inhibiting factors for the implementation of Montesori curriculum management in improving the quality of learning in Askara Montesori Kindergarten Kramatjati, East Jakarta. This study uses a descriptive qualitative approach by using data collection methods of observation, interviews and documentation. The data analysis technique stage includes data reduction, data presentation and data verification, while checking the reliability of the data is carried out by extending participation, observing accuracy, triangulation and consulting with supervisors. The results of his research indicate that the implementation of Montesori curriculum management in improving the quality of learning, namely planning includes making a training schedule for teachers, both bringing in experts and attending training outside of making head work plans / annual programs, making supervision guidelines. Then the implementation includes: supervising learning planning including RPPH, RPPM and RPPS, monitoring and evaluating by fostering teachers with motivation. Evaluation includes reporting the results of supervision starting from planning, implementing and evaluating learning, then reporting the results of child development to parents. While the driving factors for change management strategies in improving teacher performance include infrastructure and facilities that include quite complete Montesori tools.